Synthesis, crystal structure, and absolute configuration of the enantiomers of chiral drug xibenolol hydrochloride. Issue 10 (15th October 2017) - Bredikhin, Alexander A.; Bredikhina, Zemfira A.; Kurenkov, Alexey V.; Gubaidullin, Aidar T.
Graphical abstract: Abstract: Based on the features of its crystallization, racemic 3-(2, 3-dimethylphenoxy)propane-1, 2-diol2, the synthetic precursor of the chiral drug xibenolol1, was resolved into pure enantiomers by the direct method of entrainment. The enantiomers of diol2 through a Mitsunobu reaction were converted into the nonracemic 1, 2-epoxy-3-(2, 3-dimethylphenoxy)propanes ( S )- and ( R )-3, and then into the xibenolol enantiomers. Single crystals of (+)- and (−)-1 ·HCl were studied by X-ray diffraction. On the basis of the Flack parameter, the absolute ( R )- and ( S )-configurations were assigned to these compounds and to the other intermediate chiral substances. Abstract : ( S )-3-(2, 3-Dimethylphenoxy)propane-1, 2-diol: C11 H16 O3 Ee  = 98.2% ee (from HPLC) [ α ]D 20  = −13.2 ( с 1.0, MTBE) Initial source of chirality: resolution of racemic 3-(2, 3-dimethylphenoxy)propane-1, 2-diol by preferential crystallization Absolute configuration: ( S ) Abstract : ( S )-1, 2-Epoxy-3-(2, 3-dimethylphenoxy)propane: C11 H14 O2 Ee  = 96.4% ee (from HPLC) [ α ]D 20  = +16.4 ( c 1.1, EtOH), [ α ]D 20  = +6.7 ( c 1.1, CHCl3 ) Initial source of chirality: resolution of racemic 3-(2, 3-dimethylphenoxy)propane-1, 2-diol by preferential crystallization Absolute configuration: ( S ) Abstract : ( S )-1-( tert -Butylamino)-3-(2′, 3′-dimethylphenoxy)-2-propanol, ( S )-xibenolol: C15 H25 NO2 Ee  = 96.4% (from HPLC) [ α ]D 20  = −10.8 ( c 1.1, EtOH); [ α ]D 20  = −15.6 ( c 1.1, CHCl3 ) Initial source of chirality: resolution of racemic 3-(2, 3-dimethylphenoxy)propane-1, 2-diol by preferential crystallization Absolute configuration: ( S ) Abstract : ( S )-1-( tert -Butylamino)-3-(2′, 3′-dimethylphenoxy)-2-propanol hydrochloride, ( S )-xibenolol hydrochloride: C15 H25 NO2 ·HCl Ee  = 99.2% (from HPLC) [ α ]D 20  = −27.0 ( c 1.0, EtOH) Mp 146–148 °C Initial source of chirality: resolution of racemic 3-(2, 3-dimethylphenoxy)propane-1, 2-diol by preferential crystallization Absolute configuration: ( S )